1980
DOI: 10.1172/jci109833
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Enzymatic Defects in Mitochondria in Hematological Cells of Patients with Primary Sideroblastic Anemia

Abstract: A B S T R A C T Activities of mitochondrial enzymes in blood cells from 69 patients with primary sideroblastic anemia were determined to elucidate the pathogenesis ofthe disease. In erythroblasts of patients with primary acquired type the activities of both 8-aminolevulinic acid synthetase and mitochondrial serine protease were inevitably decreased. The susceptibility to the protease of apo-8-aminolevulinic acid synthetase prepared from erythroblasts of patients with this type was within the normal range, in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
2

Year Published

1982
1982
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…ALA synthetase, which catalyzes the step of ALA formation from succinyl Coenzyme A (Co-A) and glycine, is the rate-limiting enzyme in the heme synthetic pathway, and reduction of ALA synthetase activity in erythroblasts is probably the primary defect in most patients with primary SA [3-51. Recently Aoki et a1 [8] demonstrated that mitochondrial enzymes of granulocytes (eg, neutral protease, oligomycin-sensitive ATPase, etc) have low activity in hereditary and primary acquired SA. Accordingly there may be impairment of mitochondria of both erythroblasts and granulocytes in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ALA synthetase, which catalyzes the step of ALA formation from succinyl Coenzyme A (Co-A) and glycine, is the rate-limiting enzyme in the heme synthetic pathway, and reduction of ALA synthetase activity in erythroblasts is probably the primary defect in most patients with primary SA [3-51. Recently Aoki et a1 [8] demonstrated that mitochondrial enzymes of granulocytes (eg, neutral protease, oligomycin-sensitive ATPase, etc) have low activity in hereditary and primary acquired SA. Accordingly there may be impairment of mitochondria of both erythroblasts and granulocytes in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Inactuation of apo-ALA synthetase by the protease was expressed as the unit of susceptibility: 1 SU was defined as the degree of inactivation losing one-half of the activity in 30 min when 100 U of the protease was added to the incubation mixture. Other enzyme assays were measured as described earlier [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence for a low oxygen tension in the-hematopoietic stem cell (HSC) niche and a rising gradient of oxygen tension during subsequent differentiation [49][50][51][52][53][54][55][56][57], as well as reports of mitochondrial dysfunction and oxidative damage in MDS marrows [58][59][60][61][62][63][64][65][66], led us to hypothesize that MDS results from a lesion that causes apoptosis only at oxygen tensions higher than that of the HSC niche. Such a lesion would permit unlimited self-renewal of MDS-initiating cells, provided these cells stayed at an oxygen tension comparable to that of the HSC niche.…”
mentioning
confidence: 99%
“…From subcellular fracReceived for publication 2 August 1981 and in revised form 28 January 1982. tionation studies using rat erythroblasts as the material, medullasin is considered to be located on the inner mitochondrial membrane. Medullasin in erythroblasts was shown to participate in the development of a certain kind of anemia (2,3). In the course of investigating the biologic significance of medullasin in granulocytes we found that levels of medullasin in granulocytes were elevated in certain pathological conditions such as chronic inflammations and cancer (submitted for publication).…”
mentioning
confidence: 99%